Sonographic Findings of Hepatobiliary Fascioliasis Accompanied by Extrahepatic Expansion and Ectopic Lesions. (1st December 2014) - Teke, Memik; Önder, Hakan; Çiçek, Mutalip; Hamidi, Cihad; Göya, Cemil; Çetinçakmak, Mehmet Güli; Hattapoğlu, Salih; Ülger, Burak Veli
Abstract : Objectives: The aim of the study was to describe the sonographic findings of hepatobiliary fascioliasis with extrahepatic expansion and ectopic lesions. Methods: The study included 45 patients with fascioliasis. All diagnoses were confirmed via serologic enzyme‐linked immunosorbent assays. Sonographic findings in the hepatobiliary system, extrahepatic expansion, and ectopic lesions were defined. Results: The most common hepatic lesions were subcapsular localized, small, confluent, multiple hypoechoic nodules with poorly defined borders. We also detected ectopic lesion in 5 patients (11.1%) and live parasites in the gallbladder and bile duct in 11 (24.4%). Conclusions: The large spectrum of entities in the differential diagnosis of hepatobiliary fascioliasis may lead to misdiagnosis and incorrect treatment. However, the diagnosis can be made when the characteristic sonographic features are seen, such as heterogeneity of the liver with multiple poorly defined hypoechoic‐isoechoic lesions and multiple echogenic nonshadowing particles in the gallbladder or common bile ducts. Nonetheless, the differential diagnosis of fascioliasis versus other hepatic lesions may still be difficult. In these situations, pathologic confirmation should be performed to exclude the possibility of malignancy.